COMPUTED TOMOGRAPHY IN STUDYING THE SURGICAL ANATOMY OF THE POSTERIOR CRANIAL FOSSA - S. V. Ishkov (Вестник рентгенологии и радиологии)
Objective: to determine the individual roentgenometric parameters of the posterior cranial fossa and the specific features of the location of brain structures on computed tomography scans in terms of their possible use on planning surgical approaches.Material and methods. The computed tomography scans of the bony base of the posterior cranial fossa and the projection variants of the location of brain structures relative to the osseous landmarks were roentgenometrically studied in 116 patients without pathology of the cranial bones and brain.Results. The main linear (length, width, depth) and angular (a pyramidal convergence angle, a pyramidal occipital angle, a slope angle, and occipital squama inclination) roentgenometric parameters determining the shape of the posterior cranial fossa were determined. The most commonly encountered (long narrow deep, long wide fine, long narrow fine, long wide deep, and short narrow fine) shapes were identified according to the combination of the extrema of these parameters. The variants of the location of brain structures were determined within the projection planes.Conclusion. There were the roentgenometric parameters and craniocerebral ratios, which are of value in the individual planning of surgical approaches to the structures of the posterior cranial fossa.